Role of Fatty Acids in Energy Provision During Oocyte Maturation and Early Embryo Development - Sturmey, RG; Reis, A; Leese, HJ; McEvoy, TG (Reproduction in domestic animals, 2009)
While much is known about the metabolism of exogenous nutrients such as glucose, lactate, pyruvate, amino acids by oocytes and pre-implantation mammalian embryos, the role of endogenous stores, particularly lipid, has been largely overlooked. The presence of lipid within oocytes and early embryos has been long known, and comparisons between species indicate that the amounts and types of lipid present vary considerably. Large amounts of intracellular lipid can compromise the success of cryopreservation and the removal of such lipid has been the subject of considerable effort. In this review, we present evidence that strongly suggests a metabolic role for lipid, specifically with regard to energy provision, in the late-stage oocyte and the pre-implantation embryo. We focus initially on oxygen consumption as a global indicator of metabolic activity, before reviewing different approaches that either have been designed to investigate directly, or have revealed indirectly the role of endogenous lipid in energy generation. These fall under five headings: (i) fatty acid oxidation; (ii) inhibition of triglyceride oxidation; (iii) culture in the absence of exogenous substrates; (iv) cytoplasmic organization; and (v) delipidation. On the basis of the data derived from these studies, we conclude that there is strong evidence for the utilization of endogenous lipid as an energy substrate by oocytes and early embryos.